2022
DOI: 10.3390/jcm11102850
|View full text |Cite
|
Sign up to set email alerts
|

Osteolytic vs. Osteoblastic Metastatic Lesion: Computational Modeling of the Mechanical Behavior in the Human Vertebra after Screws Fixation Procedure

Abstract: Metastatic lesions compromise the mechanical integrity of vertebrae, increasing the fracture risk. Screw fixation is usually performed to guarantee spinal stability and prevent dramatic fracture events. Accordingly, predicting the overall mechanical response in such conditions is critical to planning and optimizing surgical treatment. This work proposes an image-based finite element computational approach describing the mechanical behavior of a patient-specific instrumented metastatic vertebra by assessing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…It should be noted that in the present FE model, convergence tests were performed separately on the spinal model and implant models, and the instrumented model was built based on modifications of the intact model after the convergence tests were performed and the mesh size was reduced. This approach of performing convergence tests prior to the addition of implants was also utilized in previous FE publications [ 49 , 50 , 51 , 52 ] and had an advantage in the consistency among the FE models since only part of the model was modified in each surgical construct and the other parts remained unaltered. Finally, perfect contact with tie constraints was achieved between implants and bone.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in the present FE model, convergence tests were performed separately on the spinal model and implant models, and the instrumented model was built based on modifications of the intact model after the convergence tests were performed and the mesh size was reduced. This approach of performing convergence tests prior to the addition of implants was also utilized in previous FE publications [ 49 , 50 , 51 , 52 ] and had an advantage in the consistency among the FE models since only part of the model was modified in each surgical construct and the other parts remained unaltered. Finally, perfect contact with tie constraints was achieved between implants and bone.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors make it difficult to examine the in-vivo biomechanical influence of the T1 tilt change in a noninvasive way or separate it from other cervical sagittal balance parameters in both clinical and cadaveric experiments. Finite element (FE) modeling has been widely used not only to study the biomechanical alteration at the surgically treated vetebrea under physiological ( Palanca et al, 2021 ; Dall’Ara and San Cheong, 2022 ) and pathological ( Bianchi et al, 2022 ) conditions, but also detect loading variation at adjacent segment after ACF with different surgical approaches ( Kumaresan et al, 1996 ; Hussain et al, 2013 ) or with different bone density ( Natarajan et al, 2000 ). Our previous study ( Liu et al, 2017a ) with C2–C7 FE models demonstrated that a decrease in cervical lordosis could alter the biomechanical loading pattern at adjacent segments after C4-6 ACF and it may contribute to the development of adjacent segment pathology (ASP).…”
Section: Introductionmentioning
confidence: 99%